MENGENAL á¹¢IGAT-á¹¢IGAT DALAM MEREPRESENTASIKAN HADIS: - Mulizar (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2019)
In terms of sanad and matan, or based on the strengths and weaknesses, the Hadith is divided into two groups, namely: the hadith maqb?l and the hadith mard?d. One way to find out a hadith whether the hadith is accepted or mard?d can be seen from the ??g?t. ??g?t Hadith is divided into two groups, namely ??g?t Jazm and ??g?t Tamr??. An assessment of a Hadith is incomplete if we have not discussed  ??g?t al-Jazm and  ??g?t at-Tamr??. This needs to be done to understand how the Hadith is classified. In determining the laws of  ??g?t al-Jazm and  ??g?t at-Tamr?? the Ulama of Hadith have explained that if the Hadith is a hadith ?a??f, then it is not allowed to exchange it with active sentences ( ??g?t al-jazm) such as: said the Messenger of Allah. mention the narration of the hadith ?a??f from the tabiin circles by using  ??g?t al-jazm, but by using  ??g?t at-tamr?? as the words q?la, ruwiya, ?ukiya and so forth. This article provides knowledge to the reader, namely how to recognize the traditions through the  ??g?t expressed in a hadith and give insight to the traditions that are ambiguous and mard?d through  ??g?t in a hadith, and express how the opinion of the hadith scholars about the  ??g?t.